2022
DOI: 10.3389/fcomp.2022.914525
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious load changer: Designing method to subtly influence load perception by simply presenting modified myoelectricity sensor information

Abstract: Systems of presenting myoelectricity sensor information allow users to understand the body's load for various purposes, such as medical rehabilitation and sports training. If there is a method to create the psychological phenomenon of unconsciously increasing or decreasing a user's load perception simply by changing how to present the myoelectricity sensor values, it will help design a more effective system. Therefore, we propose a method to manipulate load perception by presenting modified myoelectricity sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Similarly, the rejection of other types of augmentations apart from the cognitive ones could have excluded some hybrid cases (e.g., a cognitive augmentation for a physical limitation, like in Futami, et al [27]).…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, the rejection of other types of augmentations apart from the cognitive ones could have excluded some hybrid cases (e.g., a cognitive augmentation for a physical limitation, like in Futami, et al [27]).…”
Section: Limitationsmentioning
confidence: 99%
“…To manipulate the elapsed time sensation, some methods use tactile stimuli using wristworn devices [10,34], auditory stimuli of information devices [35], and visual icons on a head-mounted display [11,36]. To manipulate load perception such as fatigue and weight of things, there is a method that presents myoelectricity sensor information that differs from the actual measured sensor value [15,37] and a method that changes the appearance color of the object to be lifted [38]. To manipulate the user's feeling of fullness, there is a method that changes the visual size of food to eat with VR (Narumi et al [39]) and a method that changes the apparent size of the plate (Adams et al [6]).…”
Section: Related Workmentioning
confidence: 99%
“…(1) First, because computer information presentation can unintentionally affect human cognition and psychology due to unconscious phenomena (e.g., cognitive biases, psychological effects, and illusions), many recent studies have shown the importance of understanding the existence and manipulation methods of such unconscious phenomena [6][7][8][9][10][11]. For example, a previous study of information presentation systems for wearable biosensors discovered a phenomenon in which the user's mind and body unconsciously changes in accordance with the presented sensor value, even if the sensor value is different from the actual value due to a bias in the sensor value presentation algorithm (e.g., changes in anxiety with heart rate sensor presentation [12][13][14], changes in physical load with myoelectric sensor presentation [15]). The previous study also discovered a method that presents modified sensor value (i.e., false value ) to manipulate this phenomenon, which indicated that this phenomenon and method could be used for good to support the user and could be misused to harm the user.…”
Section: Introductionmentioning
confidence: 99%